2019
DOI: 10.1186/s12986-019-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intake of Trehalose induces white adipose tissue Browning and Enhances energy metabolism

Abstract: Background Trehalose is well known as a functional disaccharide with anti-metabolic activities such as suppression of adipocyte hypertrophy in mice and alleviation of impaired glucose tolerance in humans. Recently, a new type of adipocyte beige cells, involved in so-called white adipocyte tissue (WAT) browning, has received much attention as a target for adaptive thermogenesis. To clarify the relationship between adipocyte hypertrophy suppression and beige cells involved in thermogenesis, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A single dose of trehalose does not stimulate a rapid increase in blood glucose or the excessive secretion of insulin or gastric inhibitory polypeptide, which promote fat accumulation, in healthy humans [21]. Furthermore, we have recently shown that daily administration of trehalose to healthy mice consuming a standard diet induces an increase in the number of beige adipocytes, accompanied by a reduction in adipocyte hypertrophy, higher body temperature, and lower blood glucose [22]. Therefore, regular consumption of trehalose may reduce adipocyte size and induce qualitative changes in adipocytes, which may result in lower postprandial blood glucose concentration.…”
Section: Discussionmentioning
confidence: 97%
“…A single dose of trehalose does not stimulate a rapid increase in blood glucose or the excessive secretion of insulin or gastric inhibitory polypeptide, which promote fat accumulation, in healthy humans [21]. Furthermore, we have recently shown that daily administration of trehalose to healthy mice consuming a standard diet induces an increase in the number of beige adipocytes, accompanied by a reduction in adipocyte hypertrophy, higher body temperature, and lower blood glucose [22]. Therefore, regular consumption of trehalose may reduce adipocyte size and induce qualitative changes in adipocytes, which may result in lower postprandial blood glucose concentration.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of trehalose, HT29 colon cancer cells were an exception in that growth was stimulated by trehalose. Trehalose is not thought to be a major nutrient for mammalian cells but it has been reported to have a variety of effects including actions on subcellular trafficking and increasing energy metabolism and autophagy [14,15]. The action on HT29 colon cancer cells may merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We have continuously been reported that trehalose suppresses adipocyte hypertrophy and mitigates insulin resistance [1][2][3]. We also demonstrated that trehalose induces white adipose tissue (WAT) browning with suppressing white adipocyte hypertrophy, increasing body temperature, and reducing blood glucose levels even under normal dietary conditions [4]. Trehalose has an inhibitory effect on adipocyte hypertrophy that is not seen for other saccharides.…”
Section: Introductionmentioning
confidence: 90%